Assessment of evaporation and water fluxes in a column of dry saline soil subject to different water table levels. Issue 10 (21st June 2013) - Hernández‐López, María Fernanda; Gironás, Jorge; Braud, Isabelle; Suárez, Francisco; Muñoz, José Francisco
Abstract Dry saline soils are common in the arid and hyper‐arid basins located in the Chilean Altiplano, where evaporation from shallow groundwater is typically the major component of the water balance. Thus, a good understanding of evaporation processes is necessary for improving water resource planning and management in these regions. In this study, we conducted laboratory experiments with a natural saline soil column to estimate evaporation rates and assess the liquid and water vapor fluxes under different water table levels. Water content, electrical conductivity and temperature at different depths were utilized to assess the liquid and water vapor fluxes in the soil column. We observed movement of water that dissolves salts from the soil and transports them to areas in the column where they accumulate. Isothermal liquid flux was predominant, while thermal and isothermal liquid and thermal water vapor fluxes were negligible, except for deep water table levels where isothermal and thermal water vapor fluxes had similar magnitude but opposite directions. Differences observed in total fluxes for all water table levels were due to different upward and downward fluxes, which depend on changes in water content and temperature within the soil profile. Both the vapor flux magnitude and direction were found to be very sensitive to the choice of empirical parameters used in flux quantification, such as tortuosity and the enhancement factor for local temperature gradients in the air phase within the column. Copyright © 2013 John Wiley & Sons, Ltd.